2019
DOI: 10.1186/s13244-019-0753-3
|View full text |Cite
|
Sign up to set email alerts
|

Blood finds a way: pictorial review of thoracic collateral vessels

Abstract: In the healthy patient, blood returns to the heart via classic venous pathways. Obstruction of any one of these pathways will result in blood flow finding new collateral pathways to return to the heart. Although significant anatomic variation exists and multiple collateral vessels are often present in the same patient, it is a general rule that the collateral pathways formed are a function of the site of venous blockage. Therefore, knowledge of typical collateral vessel systems can provide insight in localizin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…The azygos vein is formed by the union of the right subcostal and right ascending lumbar veins. It is a collateral venous pathway of great importance, as it serves as a connection between the superior and inferior vena cava [12]. Therefore, an obstruction of the SVC below the insertion of the azygous vein is less tolerated and result in more intense symptoms compared to a block above the orifice of the azygos, where blood is diverted to the heart via the inferior vena cava and azygous system [13].…”
Section: Review Anatomy and Physiologymentioning
confidence: 99%
“…The azygos vein is formed by the union of the right subcostal and right ascending lumbar veins. It is a collateral venous pathway of great importance, as it serves as a connection between the superior and inferior vena cava [12]. Therefore, an obstruction of the SVC below the insertion of the azygous vein is less tolerated and result in more intense symptoms compared to a block above the orifice of the azygos, where blood is diverted to the heart via the inferior vena cava and azygous system [13].…”
Section: Review Anatomy and Physiologymentioning
confidence: 99%
“…Originally, SVC syndrome was commonly described as secondary to infection [ 1 , 2 ]. However, SVC became associated with malignancy, most commonly primary lung malignancies [ 6 ]. Obstruction of the SVC leading to superior vena cava syndrome is an oncological emergency [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4] The US-guided percutaneous technique for CVC in pediatric patients has been reported to be safe with reduced operating times, preserved vein size and no significant increase in immediate and late complications, as the technique constitutes the standard of care in pediatric, neonatal and adult patients. 5 Studies have shown a relevant alteration rate of 22% and 26% in the IJV after removal of catheters, which were placed using the open venous cutdown technique. 2,3 In the study by Ritz et al, 2 the occlusion rate was reported as 9% in pediatric patients, whereas; that in the subgroup of patients <1 year of age was 17.6%.…”
Section: Discussionmentioning
confidence: 99%
“…The Journal of Vascular Access 23 (5) performed using L12-4 MHz linear probe (GE-LOGIQ) after positioning the patient in the supine position on a gel pad, aligning the torso, and lower extremities, with an additional roll under the shoulders supporting the neck while lowering and rotating the head to the contralateral side. Both right and left IJVs were not visible to guide toward the brachiocephalic veins (BCVs) (Figure 1(a) and (b)).…”
mentioning
confidence: 99%